THE INFLUENCE OF SCIENCE, TECHNOLOGY, AND SOCIETY (STS) ON STUDENT LEARNING OUTCOMES IN THE SUBCONCEPT OF GLOBAL WARMING - Mufti Ali (Jurnal Life Science : Jurnal Pendidikan dan Ilmu Pengetahuan Alam, 2019)
ABSTRACTThe purpose of this study is to determine the effect of science technology and society (STS) learning model on the learning outcomes of student on the sub concepts of the global warming in class VII SMP Negeri 5 Tasikmalaya.This research was conducted in December 2017 until Juni 2018 at SMP Negeri 5 Tasikmalaya. The research method used is the "true experiment" method with the population of all classes VII SMP Negeri 5 Tasikmalaya, as many as 12 classes with the number of students 368 people. Samples were taken using cluster random sampling technique of 2 classes, namely class VII G as experimental class and VII F as control class. The instrument used is the test technique of student learning outcomes on the sub concepts global warming. This written test be in the form of multiple choice with four choices. Data analysis technique used is t test with α 0.05.The results showed that there is influence of science technology and society (STS) learning model on student learning outcomes on the sub concepts of the global warming in class VII SMP Negeri 5 Tasikmalaya Keywords : science technology and society (STS) learning model, learning    outcomes of students, and global warming.